PEMBINAAN LAPORAN KEUANGAN DALAM MENINGKATKAN KINERJA MANAJEMEN KOPERASI - Dadi Akhmad Perdana; Putu Rani Susanthi; Yuliadi Yuliadi; Yossi Hendriati; Merline Julianti (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
The good financial statement reports is very needed by every management of the company or any organization to evaluate the performance of management. To see and evaluate the financial condition and performance of the company or organization, the numbers that recorded in the financial statements will be more meaningful if these numbers can be compared with each other, for example comparing financial performance in the current year with the previous year. So that it can be seen whether the performance this current year is better or has decreased compared to previous years.The financial statement reports also used in other institutions or organizations such as cooperatives. Cooperatives are one of the institutions that have financial transactions in their operations, so they are requiring a record of financial statement reports. And by recording good financial statement reports, cooperative performance can be evaluated from year to year.